The Development of Home Nursing Care Module for Patients with Pulmonary TB in Bima City, West Nusa Tenggara - Abdul Haris; Muhtar Muhtar; Ahmad Ahmad; Aan Dwi Sentana (Health Notions, 2019)
The complete treatment was one of the main strategies in controlling and terminating the chain of transmission of pulmonary TB. Self-care behavior carried out by patients and families during the treatment process was the key to the success of pulmonary TB treatment. One effort to improve sufferers' self-care was through health education which was combined with the module as the patient's handler. Using the action research method with quantitative and qualitative approaches, this study involved health workers, PMOs and pulmonary TB patients undergoing treatment, with quantitative data analysis using triangulation techniques. The results of the study addressing the needs of nursing care for patients with pulmonary tuberculosis based on the results of a focus group discussion include knowledge about pulmonary TB disease, how to deal with symptoms that were often experienced, and actions or skills in self-care while at home. The conclusion of this study was the development of nursing care modules at home for pulmonary TB patients intended to improve the ability of self-care patients to cure illness. Keywords: nursing care module; pulmonary TB